1997
DOI: 10.1086/516068
|View full text |Cite
|
Sign up to set email alerts
|

Postsurgical Mediastinitis: A Case‐Control Study

Abstract: We report the results of a case-control study of postsurgical mediastinitis (PSM) that we conducted from 1985 to 1993. The incidence of PSM was 2.2% (81 of 3,711 cases who underwent sternotomy); we analyzed the findings for 73 cases and 73 controls. Univariate analysis revealed that the risk factors for PSM were emergency surgery (27% of cases vs. 13% of controls), New York Heart Association functional class IV (46.5% vs. 21.9%), heart transplantation (12% vs. 0), and coronary artery bypass graft (CABG) surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(51 citation statements)
references
References 18 publications
3
42
0
6
Order By: Relevance
“…These findings are in agreement with those of other studies of postsurgical mediastinitis (7,13). Coagulase-negative Staphylococcus was the main organism isolated from EPW cultures (74.9%).…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in agreement with those of other studies of postsurgical mediastinitis (7,13). Coagulase-negative Staphylococcus was the main organism isolated from EPW cultures (74.9%).…”
Section: Discussionsupporting
confidence: 92%
“…Those often include purulent discharge from the mediastinal area (11,12,16), in some cases together with fever (Ն38°C) and sternal dehiscence (4,10,18). L'Ecuyer et al, who did not include purulent discharge or sternal dehiscence in their criteria for chest infection, found that those signs occurred in only 67% and 26% of the patients, respectively (8).…”
mentioning
confidence: 99%
“…aeruginosa. [7][8][9] So our regime of antibiotics containing teicoplanin and meropenem was justified to use as prophylaxis of all types of open Heart surgery. Glycopeptides have some adverse events particularly 'red man' syndrome and nephrotoxicity.…”
Section: Antibiotic Regimementioning
confidence: 99%
“…3,4 Staphylococcus aureus and Staphylococcus epidermidis are the most common culprit in post cardio-thoracic SSI. [5][6][7][8][9] Other micro-organisms, including diptheroides, aerobic and anaerobic streptococci and enteric gram-negative bacilli are also involved. [10][11][12] In an attempt to prevent both wound infections and prosthetic valve endocarditis cardiac surgery presently administer antibiotics to virtually all patients undergoing cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%